Indeks Massa Tubuh, Rasio Lingkar Pinggang, Tinggi Badan terhadap Sindrom Metabolik pada Stunted Obesity - Nur Adriyani, Fauziah Hanum; Hikmanti, Arlyana; Dewi, Feti Kumala (Midwifery Care Journal, 2025)
Â Stunted was a major nutrition problem in Indonesia. Obesity caused metabolic changes caused by endothelial dysfunction and oxidative stress mechanisms defined by waist size, HDL, triglycerides, calm blood glucose, and blood pressure. The purpose of this study is to determine the relationship between stubborn obesity and metabolic syndrome in female adolescents. Study design was case control with 150 students in the Banyuma district. Subject selection was performed using multistage random samples. The case group was 75 students who inhibited obesity, and the control group was 75 students with stunted and non-attended. Determine nutritional status by measuring size, weight and waist size. Metabolic syndrome was determined using three criteria: obesity, blood glucose level above 100 mg/dL, and lipid profile. Triglyceride levels â‰¥150 mg/dL and HDL levels â‰¤ 0 mg/dL; Data were analyzed on a descriptive test for univariate analysis and a Chi-square test for determining relationships.The mean values of HDL levels (39.80 Â± 3.96 mg/dL), fasting blood sugar (112.6 Â± 8.75 mg/dL), and triglycerides (102.34 Â± 17.54 mg/dL) in the case group were higher than the mean values in the control group. There is a relationship between Stunted obesity and the incidence of metabolic syndrome in adolescents with Ï = 0.0479. This indicates that there is a higher risk of experiencing metabolic syndrome in the case group.